2011
DOI: 10.1177/2040622310397636
|View full text |Cite
|
Sign up to set email alerts
|

Latest advances on interventions that may prevent, delay or ameliorate dementia

Abstract: Abstract:Objectives: In this paper we aim to: (1) identify and review midlife risk factors that may contribute to the development of dementia and that may be amenable to intervention; (2) review advances made in our understanding of the most common cause of dementia, Alzheimer's disease (AD), where current pharmacological studies have aimed to modify the disease course; and (3) explore other interventions that may slow cognitive decline in those with AD. Methods: A review of the literature was conducted to loo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 96 publications
0
13
0
Order By: Relevance
“…Early diagnosis provides opportunities for symptomatic treatment, participation in clinical treatment trials, long‐term care planning, estate planning, and often provides the answer as to why a loved one has become forgetful, irritable, paranoid, anxious, or depressed. Further, early intervention to improve the general health of the patient through management of comorbidities and increasing physical activity, along with other lifestyle modifications, may delay the onset of more severe symptoms …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Early diagnosis provides opportunities for symptomatic treatment, participation in clinical treatment trials, long‐term care planning, estate planning, and often provides the answer as to why a loved one has become forgetful, irritable, paranoid, anxious, or depressed. Further, early intervention to improve the general health of the patient through management of comorbidities and increasing physical activity, along with other lifestyle modifications, may delay the onset of more severe symptoms …”
Section: Discussionmentioning
confidence: 99%
“…Second, there are several symptomatic therapies that can help manage the symptoms of cognitive impairment due to ADRD, and there are many other treatment options that can address the behavioral and psychiatric symptoms of dementia effectively. Third, dementia patients’ quality of life may be enhanced by nonpharmacologic management of comorbidities and lifestyle modifications such as increasing physical activity . Additionally, the personality, behavioral, and functional changes that often accompany dementia may be less upsetting for caregivers if they are explained by a diagnosis.…”
mentioning
confidence: 99%
“…Optimum and aggressive control of hypertension, diabetes, weight, smoking, and vascular risk factors and the need for exercise have been identified as potential preventative strategies. 63,64 Vascular dementia accounts for about 30% of the total dementia prevalence. 3 Vascular risk factors were most prevalent in our study.…”
Section: Demographic Risk Factorsmentioning
confidence: 99%
“…cancer) and rarer forms of dementia (Korsakoff's syndrome, dementia due to HIV, normal pressure hydrocephalus, CADASIL); animal studies and non-English language articles. As effects of antihypertensive drugs on the progression of dementia have been reviewed elsewhere [8][9] , they were excluded from the literature analysis.…”
Section: Eligibilitymentioning
confidence: 99%
“…Previous reviews have proposed but not proven that such treatment might delay the onset of dementia [8][9] . Another review concluded that there is no convincing evidence of the effectiveness of antihypertensive therapy in the reduction of cardiovascular and cerebrovascular events in people with dementia 56 , which our review has confirmed.…”
Section: Orthostatic Hypotensionmentioning
confidence: 99%